2017
DOI: 10.3390/nu9080904
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics Prevent Late-Onset Sepsis in Human Milk-Fed, Very Low Birth Weight Preterm Infants: Systematic Review and Meta-Analysis

Abstract: Growing evidence supports the role of probiotics in reducing the risk of necrotizing enterocolitis, time to achieve full enteral feeding, and late-onset sepsis (LOS) in preterm infants. As reported for several neonatal clinical outcomes, recent data have suggested that nutrition might affect probiotics’ efficacy. Nevertheless, the currently available literature does not explore the relationship between LOS prevention and type of feeding in preterm infants receiving probiotics. Thus, the aim of this systematic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(75 citation statements)
references
References 77 publications
(215 reference statements)
0
73
0
2
Order By: Relevance
“…Well-established strategies for NEC prevention should continue to be reinforced, such as giving human breast milk rather than formula, and use of standardised feeding regimens 20 26. Furthermore, there is evidence that use of probiotics can prevent LOS in high-risk preterm infants 24 27 28…”
Section: Discussionmentioning
confidence: 99%
“…Well-established strategies for NEC prevention should continue to be reinforced, such as giving human breast milk rather than formula, and use of standardised feeding regimens 20 26. Furthermore, there is evidence that use of probiotics can prevent LOS in high-risk preterm infants 24 27 28…”
Section: Discussionmentioning
confidence: 99%
“…Among human milk-fed infants, mixtures of probiotic and not single-strain products were effective in reducing late onset sepsis as well. 10 In diarrheal patients of our study, nutritional status was also observed and the results showed that those 25 group A and 23 group B patients who had normal nutritional status had no dehydration as well. Similarly, moderate malnutrition noted in 12 group A and 15 group B patients had some dehydration.…”
Section: Assessment Of Dehydrationmentioning
confidence: 50%
“…L. acidophilus/B. infantis may require the complex composition of human milk to exert a growth-promoting effect and to stabilize gut immunity in order to prevent translocation sepsis [6,7,33]. Human milk includes endogenous probiotics, prebiotic carbohydrates, stem cells, and a concert of bioactive human milk factors (e.g., S100 A8/9 [34]) that have direct or indirect effects on the vulnerable host-gut microbiota interplay [11].…”
Section: Discussionmentioning
confidence: 99%